The religious thought of Chu Hsi - Ching, Julia (Oxford University Press, 2000)
Recognized as one of the greatest philosophers in classical China, Chu Hsi (1130-1200) is known in the West through translations of one of his many works, the Chin-ssu Lu. This study offers an examination of Chu Hsi's religious thought, based on readings of both primary and secondary sources.